Microplastic distribution and its implications for human health through marine environments - Ho, Chia Min; Feng, Weiying; Li, Xiaofeng; Ngien, S. K.; Yu, Xuezheng; Song, Fanhao; Yang, Fang; Liao, Haiqing (Elsevier, 2025)
Microplastics are pervasive pollutants in the ocean, threatening ecosystems and human health through bioaccumulation and toxicological effects. This review synthesizes recent findings on microplastic distribution, trophic transfer, and human health impacts. Key findings indicate that microplastic abundance is highest in the Indian and Pacific Oceans, particularly in seawater and sediment. Morphologically, fibers and fragments dominate, with polypropylene, polyethylene, and polyester being the most prevalent polymers. Smaller particles (<1 mm) undergo long-range transport via ocean currents, while biofouling accelerates vertical sinking. Trophic transfer studies confirm microplastic ingestion across marine food webs. Human exposure is associated with seafood consumption, inhalation of airborne particles, and potential dermal contact, particularly in marine environments. These exposures can lead to adverse health effects, including inflammation, organ damage, respiratory issues, oxidative stress, and metabolic disruptions. Finally, this review explores potential strategies for minimizing human exposure to microplastic pollution in marine environments, paving the way for further research in this critical area.